NEW BIOSTRATIGRAPHIC DATA ON THE TRIASSIC OF THE MARATHOVOUNO HILLOCK AREA (CHIOS ISLAND, GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The Island of Chios (northern Egean Sea, Greece) is known for a well-preserved Paleozoic to Mesozoic sedimentary sequence. This paper is  focused on the micropaleontology and biostratigraphy of the Marmarotrapeza Formation (Lower/Middle Triassic) and of the overlying  Bunte Serie Unit (Middle Triassic), outcropping near the Marathovouno  Hillock section proposed by Assereto (1974) as type-section for the Aegean substage (Lower Anisian). The results obtained allow to better define the age of the Bunte Serie basin and of the coeval carbonate platform, which ranges from the Anisian (?Pelsonian) to the Norian-?Rhaetian.
Keywords: Triassic; Foraminifers; Biostratigraphy; Chios; Greece.